Dynamic safety capability and organizational management systems: An assessment tool to evaluate the "fitness-to-operate" in high-risk industrial environments - Curcuruto, M.; Griffin, Mark; Hodkiewicz, M. (The Italian Association of Chemical Engineering, 2017)
© Copyright 2017, AIDIC Servizi S.r.l. Aim: The paper outlines a systemic approach to understanding and assessing safety capability in high-risk industries, like off-shore oil, gas industry, chemical operators. The "Fitness to Operate" framework (acronym: FTO) (Griffin et al., 2014) has been recently defined by three enabling capitals that create safety capability: organizational capital, social capital, and human capital. Furthermore, each type of capital is identified by more specific dimensions based on current theories of safety, management, and organizational processes. In this paper, we will present a multidimensional assessment tool that offers a comprehensive picture of safety capability by real industrial operators in order to understand and evaluate their "fitness-to-operate" (FTO). Method: This current paper aims to describe the multi-phase development process of a FTO assessment tool in the format of a multidimensional survey questionnaire. A) The first research phase consists of the item generation of a large prototype pool with about 200 contents-items covering the 27 dimensions of the conceptual representation of the FTO framework. This initial pool was developed by a team of academic researchers, through a deductive process, and in the light of the original FTO conceptualization, as defined by Griffin and colleagues (2014) B) In a second research phase, the initial pools of items were re-examined by a new pool of academic researchers, assessing the quality of the contents, and in order to refine the extensive version of the prototype, eliminating potential redundancies and inadequate items. C) In a third phase with structured interviews to a pool of industrial experts (senior safety managers; senior executives), the authors assessed the quality of the prototype tool developed by the academic researchers, in order to evaluate and ranks the items of the prototype in term of quality, in order to define and identify a shorter version of the prototype. All the items were assessed by the experts considering criteria such as: i) relevance ii) clearness iii) verifiability iv) specificity v) ease of answer. Implications: Overall, the FTO assessment tool enables a comprehensive coverage of factors that influence short-term and long-term safety outcomes. The tool may serve to help safety regulators and industrial operators to understand, assess, and eventually implement and improve the safety capability and fitness-to-operate in complex industrial and organizational contexts.